(untitled) (Orfeu, 2025)
Although Daniel Moreira and co-authors (2021) have already addressed the systemic modeling of musical texture, the modeling of certain aspects of this dimension, such as the contour of the complexity levels of rhythmic partitioning and density-compression, remains unexplored. Systemic Modeling is a pre-compositional methodology that examines the structure of a musical work by employing specific parameters to generate a new composition, using its abstract relationships as a foundation. In this study, we describe and discuss the process of systemic modeling of texture contour from the perspective of complexity levels in rhythmic partitioning and density-compression in the first movement of String Quartet No. 17 by Heitor Villa-Lobos, with the aim of generating the piece Devaneios 5. We conclude that systemic modeling, from the perspective of texture contours, has the potential to foster new creative compositional approaches.